The potency of common proinflammatory cytokines measurement for revealing the risk and severity of anxiety and depression in psoriasis patients. Issue 9 (9th August 2022) - Tong, Nannan; Zhang, Yu; Yang, Anping; Dai, Xiaoli; Hao, Siyu
Abstract: Objective: Proinflammatory cytokines mediate anxiety and depression in various ways, such as immunity, inflammation, and the hypothalamic–pituitary–adrenal axis. This study intended to further explore the linkage of common proinflammatory cytokine levels with anxiety and depression in psoriasis patients. Methods: Totally, 150 psoriasis patients and 50 healthy controls (HCs) were included; the serum samples were collected, then common proinflammatory cytokines were measured by ELISA. Hospital Anxiety and Depression Scale (HADS) was assessed. Results: HADS‐anxiety (HADS‐A) score, HADS‐depression (HADS‐D) score, TNF‐α, IL‐1β, IL‐6, IL‐12, IL‐17A, and IL‐23 were all increased in psoriasis patients compared to HCs (all p  < 0.05). In psoriasis patients, TNF‐α ( p  = 0.001), IL‐12 ( p  = 0.035), and IL‐17A ( p  < 0.001), but not IL‐1β ( p  = 0.255), IL‐6 ( p  = 0.248), and IL‐23 ( p  = 0.216), were positively linked to HADS‐A score. Meanwhile, TNF‐α ( p  = 0.007) and IL‐17A ( p  = 0.007) were enhanced in psoriasis patients with anxiety in contrast to those without anxiety; whereas IL‐1β ( p  = 0.178), IL‐6 ( p  = 0.360), IL‐12 ( p  = 0.239), and IL‐23 ( p  = 0.450) were not different. TNF‐α ( p  < 0.001), IL‐1β ( p  = 0.013), Il‐17A ( p  < 0.001), and IL‐23 ( p  = 0.023), but not IL‐6 ( p  = 0.143) and IL‐12 ( p  = 0.158), were positively linked to HADS‐D score. Concurrently, TNF‐α ( p  = 0.015), IL‐17A ( p  < 0.001), and IL‐23 ( p  = 0.017) were climbed in psoriasis patients with depression by comparison to those without depression; whereas IL‐1β ( p  = 0.113), IL‐6 ( p  = 0.237), IL‐12 ( p  = 0.660) did not differ. Conclusion: TNF‐α, IL‐17A, and IL‐23 increments reflect anabatic anxiety and depression in psoriasis patients, uncovering the potency of proinflammatory cytokines measurement for monitoring or even preventing psoriasis patients' anxiety and depression. Abstract : Figure 1. TNF‐, IL‐12, and IL‐17A were positively linked to HADS‐A score in psoriasis patients. Association of TNF‐ (A), IL‐1 (B), IL‐6 (C), IL‐12 (D), IL‐17A (E), and IL‐23 (F) with HADS‐A score in psoriasis patients.